Lacticaseibacillus rhamnosus Reduces the Pathogenicity of Escherichia coli in Chickens - Guo, Mengjiao; Zhang, Congyue; Zhang, Chengcheng; Zhang, Xiaorong; Wu, Yantao (Frontiers in Microbiology, 2021)
Lacticaseibacillus rhamnosus is a recognized probiotic that is widely used in scientific research and clinical applications. This study found that the Lacticaseibacillus rhamnosus GG (LGG) strain can reduce the adhesion of Escherichia coli (E. coli) to primary chicken intestinal epithelial cells by 75.7% and inhibit 41.7% of the E. coli that adhere to intestinal epithelial cells. Additionally, LGG showed strong inhibitory ability on the growth of E. coli, Staphylococcus aureus, Salmonella Paratyphi B, and Salmonella Enteritidis in vitro. Furthermore, the influence of LGG on the growth performance, intestinal flora, immunity, and disease resistance of chickens was explored. Chickens fed with LGG exhibited increased average daily weight gain and concentrations of sIgA, IgG, and IgM than did controls. After 21 days of feeding, a diet with LGG increased the diversity of intestinal microbiota and maintained intestinal health. Moreover, LGG promoted immunologic barriers by up-regulating cytokines and chemokines via Toll-like receptor. The major pro-inflammatory factors, including Myd88, NF-κB, Il6, and Il8, were up-regulated compared to controls. After being challenged with E. coli, the survival rate of chickens fed with LGG was significantly higher than those in the control group, and decreased numbers of E. coli were detected in the heart and lungs of the LGG group. In summary, oral administration of LGG to chickens could improve growth performance, maintain intestinal homeostasis, and enhance innate immune response and disease resistance.